2020
DOI: 10.3390/diagnostics10050267
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Trans-Abdominal and Water-Immersion Ultrasound Images of Diseased Intestinal Segments in Crohn’s Disease

Abstract: The aim of this study is to clarify whether trans-abdominal ultrasound (TAUS) can reflect actual intestinal conditions in Crohn’s disease (CD) as effectively as water-immersion ultrasound (WIUS) does. This retrospective study enrolled 29 CD patients with 113 intestinal lesions. Five ultrasound (US) parameters (distinct presence/indistinct presence/disappearance of wall stratification in the submucosal and mucosal layers; thickened submucosal layer; irregular mucosal surface; increased fat wrapping around the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The ultrasound pattern evocating a possible fistula may not be univocal, and several possible signs have been proposed, often related to the experience of the examiner [21]. Indeed, some further evidence showed a sensitivity close to 70% for detecting fistulae, even when other ancillary techniques, such as water immersion, were adopted [22]. However, results are conflicting in the literature, as an additional study showed a sensitivity of 100% and a specificity of 98% [23], thus underlining that the expertise of the observer may be a main issue and a bias to be highlighted when reporting results in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound pattern evocating a possible fistula may not be univocal, and several possible signs have been proposed, often related to the experience of the examiner [21]. Indeed, some further evidence showed a sensitivity close to 70% for detecting fistulae, even when other ancillary techniques, such as water immersion, were adopted [22]. However, results are conflicting in the literature, as an additional study showed a sensitivity of 100% and a specificity of 98% [23], thus underlining that the expertise of the observer may be a main issue and a bias to be highlighted when reporting results in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, ultrasound is more sensitive than X-ray examination as it is able to reveal gas accumulation in the abdominal cavity and the intestinal wall swelling; thus, the diagnosis can be made at the early stage of the disease. 13 The combined use of CEUS, ultrasound-guided diagnostic puncture and drainage not only can identify quickly the nature of the lesion, but contributes to the success of further systematic therapy as well. 14,15 A drainage tube placed at the external fistula can be used to locate the fistula by using contrast under X-ray examination.…”
mentioning
confidence: 99%